Radical vulvectomy with a bilateral pudendal flap in the treatment of a vulvar cancer relapse. Issue 2 (4th January 2017) - de la Noval, Begoña Díaz
Key Clinical Message: One of the main risk factors for relapse in vulvar cancer after lymph‐node metastases is free surgical margins. In the case of a relapse, radical vulvectomy with perineal reconstruction is the first choice. Perineal reconstruction is usually indicated in relapse and unusual for a first surgery, except extensive damage1 2 3 4 5 . Abstract : One of the main risk factors for relapse in vulvar cancer after lymph‐node metastases is free surgical margins. In the case of a relapse, radical vulvectomy with perineal reconstruction is the first choice. Perineal reconstruction is usually indicated in relapse and unusual for a first surgery, except extensive damage.